2013
DOI: 10.1371/journal.ppat.1003809
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii-Induced Activation of EGFR Prevents Autophagy Protein-Mediated Killing of the Parasite

Abstract: Toxoplasma gondii resides in an intracellular compartment (parasitophorous vacuole) that excludes transmembrane molecules required for endosome - lysosome recruitment. Thus, the parasite survives by avoiding lysosomal degradation. However, autophagy can re-route the parasitophorous vacuole to the lysosomes and cause parasite killing. This raises the possibility that T. gondii may deploy a strategy to prevent autophagic targeting to maintain the non-fusogenic nature of the vacuole. We report that T. gondii acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
144
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(156 citation statements)
references
References 81 publications
9
144
1
Order By: Relevance
“…Similar effects on invasion due to deletion of other microneme proteins such as M2AP (9) or MIC3 (7) also cause delayed lethality, presumably due to a slower progression of the infection leading to more effective immune clearance. A recent study showed that EGF-containing MICs, including MIC3, activate Akt signaling via EGF receptors to diminish autophagic killing of the parasite in host cells (34). However, recombinant TgSPATR did not promote epidermal growth factor receptor (EGFR)-Akt activation (L. Muniz-Feliciano, J.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects on invasion due to deletion of other microneme proteins such as M2AP (9) or MIC3 (7) also cause delayed lethality, presumably due to a slower progression of the infection leading to more effective immune clearance. A recent study showed that EGF-containing MICs, including MIC3, activate Akt signaling via EGF receptors to diminish autophagic killing of the parasite in host cells (34). However, recombinant TgSPATR did not promote epidermal growth factor receptor (EGFR)-Akt activation (L. Muniz-Feliciano, J.…”
Section: Discussionmentioning
confidence: 99%
“…Parasite avoidance of the phagolysosome is inhibited by treatment of cells with tyrosine kinase inhibitors, and the epidermal growth factor (EGF) receptor, which is a receptor tyrosine kinase, was identified as at least one target of these inhibitors (44). Significantly, parasite growth was attenuated in cells transfected with small interfering RNAs (siRNAs) targeting the EGF receptor and the PVs in these cells appeared as if they were undergoing autophagic destruction.…”
Section: The Host Plasma Membrane As a Key Target For Toxoplasma To Rmentioning
confidence: 99%
“…These data support a model where EGF/AKT signaling either prevents the invading parasite from entering the endolysosomal pathway or prevents lysosomal recruitment to the PV. While the parasite ligand(s) that activates the EGF receptor is unknown, the receptor is not activated by parasites with knockout mutations in the MIC1 and MIC3 micronemal proteins (44).…”
Section: The Host Plasma Membrane As a Key Target For Toxoplasma To Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Micronemal proteins (MICs) are serially secreted from micronemes during T. gondii infection, and play a significant role in the asexual life cycle of this parasite by mediating parasite invasion, motility, and attachment to host cells (Besteiro et al, 2011;Muniz-Feliciano et al, 2013;Sharma and Chitnis, 2013). As an important member of the MIC family, MIC8 participates in T. gondii invasion through interaction with soluble MIC3 (Cérède et al, 2002;Kessler et al, 2008), and is a potential vaccine candidate against acute and chronic T. gondii infections in a mouse model (Liu et al, 2010;Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%